Nasza Ameryka wyobrażona : Polskie spotkania z amerykańską kulturą popularną po roku 1918 - Szymkowska-Bartyzel, Jolanta (Wydawnictwo Księgarnia Akademicka, 2015)
OUR IMAGINED AMERICA: POLISH ENCOUNTERS WITH AMERICAN POPULAR CULTURE AFTER 1918 The presented monograph attempts to describe and critically reflect on the presence of American popular culture in Poland in various historical periods after 1918. It systematizes Polish experience with American cultural texts, and analyzes their forms and functions within the context of changing times and different political and economic systems. The concept of the encounter was used primarily because of its capacity and non-evaluative character. An encounter means contact between at least two parties – people, events, objects – and the interaction which such contact generates. Reception of a cultural text is always a two-way interaction. The recipient concretizes and interprets the text, which acquires new meanings. As a result, American cultural texts gain new meanings not only marked by Polish specificity, but also new added features and values that might not occur at all in other cultures. The key concept used in discussing Polish encounters with American popular culture is the concept of an “Imagined America,” a form of social images and notions concerning the United States and its culture, people, lifestyle, etc. – a construct which was established in the collective imagination of Polish people. The Polish “Imagined America” has been largely based on the texts of popular culture icons, symbols and values evoked by this culture, and played a significant role in organizing social emotions, behavior and aspirations in various periods of Polish history. Polish encounters with American culture in many areas differ from those in Western Europe. An experience that significantly contributed to this difference was the nearly fifty-year-long domination of the communist system, which partially excluded Poles from participation in the changes that occurred in post-war Western Europe, namely the dynamic spread of the American influence in various areas of life – both those associated with the presence of American popular culture, as well as changes in business, education and political life. This half-century of experience arising from operation in a different political and economic system not only determined the character of the presence of American culture in Poland, but also the attitude of Polish people to that culture.